1990
DOI: 10.1042/bj2710387
|View full text |Cite
|
Sign up to set email alerts
|

Acinar zonation of cytosolic but not organelle-bound activities of phosphoenolpyruvate carboxykinase and aspartate aminotransferase in guinea-pig liver

Abstract: In human liver, unlike in rat liver, there is no apparent acinar heterogeneity of total cellular activity of phosphoenolpyruvate carboxykinase [Wimmer, Luttringer & Columbi (1990) Histochemistry 93, 409-415]. Since the intracellular compartmentation of phosphoenolpyruvate carbonxykinase differs in rat and human liver, we examined the acinar heterogeneity of cytosolic and organelle-bound activities of this enzyme in the guinea pig, which shows a more similar intracellular compartmentation of enzyme activity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…The absence of predominance of alanine synthesis from lactate and pyruvate plus ammonia in the periportal region is an unexpected phenomenon by virtue of the reported predominance of alanine aminotransferase in the periportal region (1,5,11,32,36,40). This observation is a clear indication that data on enzyme activity or expression alone cannot be extrapolated unconditionally to the living cell.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The absence of predominance of alanine synthesis from lactate and pyruvate plus ammonia in the periportal region is an unexpected phenomenon by virtue of the reported predominance of alanine aminotransferase in the periportal region (1,5,11,32,36,40). This observation is a clear indication that data on enzyme activity or expression alone cannot be extrapolated unconditionally to the living cell.…”
Section: Discussionmentioning
confidence: 91%
“…The results of the present study confirm that gluconeogenesis and the associated oxygen uptake tend to predominate in the periportal region. Moreover, several investigators have found that the alanine aminotransferase activity predominates in periportal hepatocytes (1,5,11,32,36,40). Furthermore, no predominance of ureagenesis in the periportal region was found, except for conditions of high ammonia concentrations plus oxidizing conditions induced by pyruvate.…”
mentioning
confidence: 99%
“…PEPCK-M expression is essentially constitutive [31] and expressed homogenously across the hepatic acinus [41]. In contrast, PEPCK-C is most richly express in the periportal region of the hepatic acinus and its hormonal and nutritional regulation is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques used in the study of hepa tocellular heterogeneity have been reviewed previously [10,23], The distribution of en-zyme activities and amounts was studied us ing histochemical [1][2][3][4], immunohistochem ical [24][25][26] and microdissective/microbiochemical techniques [26][27][28][29][30][31][32][33][34][35][36][37] as well as the digitonin dual pulse perfusion method [38], Periportal and perivenous hepatocytes were characterized functionally by using ortho-(= antera-) and retrograde liver perfusions, periportal-and perivenous-enriched hepato cyte populations [39][40][41][42][43] and periportal-like and perivenous-like hepatocytes induced in long-term primary culture [44], They were also characterized by applying noninvasive techniques with micro-light guides and with miniature oxygen electrodes positioned in periportal and perivenous areas at the liver surface for the measurement of surface fluo rescence and surface reflectance and of sur face oxygen tension, respectively [8] , 20 40 60 80 100 100 80 60 40 20 Blood level (%) Fig. 1.…”
Section: Methods For Studying Liver Cell Heterogeneitymentioning
confidence: 99%
“…1). Succinate dehydroge nase [4], a key enzyme of the citrate cycle, and glucose-6-phosphatase [3,27], fructose-1,6-bisphosphatase [25,28,29] as well as phosphoenolpyruvate carboxykinase [24,30,31,43], key enzymes of gluconeogenesis, were shown using histochemical, immuno histochemical or microbiochemical/microdissective techniques to be localized mainly in the periportal zone. Conversely, glucoki nase [25,28,32,33] and pyruvate kinase isoenzyme L [26,30,31,34], key enzymes of glycolysis, were located predominantly in the perivenous zone.…”
Section: Enzymesmentioning
confidence: 99%